Immunopotentiating effect of Inonotus obliquus fermentation products administered at vaccination in chickens. (October 2018) - Zhang, Lin; Lin, Dongmei; Li, Haiyan; Yu, Sen; Bai, Junping; Ding, Zhiyong; Wu, Jiaqiang
Abstract: Vaccination is an important approach for the control of avian viral diseases. The aim of this study was to evaluate the immune-potentiating effect of oral administration of Inonotus obliquus fermentation products (IOFP) at vaccination in chickens. In total, 120 one-day-old specific-pathogen-free chickens were randomly assigned to six groups: groups 1 to 3 were vaccinated with Newcastle disease virus (NDV) LaSota live vaccine via intranasal and eye-dropped route at seven days of age, and boosted two weeks later. Before each immunization, chickens in groups 1 and 2 were orally administered 0.8% IOFP and 0.2% astragalus polysaccharide (APS) in their diets, respectively, for seven consecutive days and group 3 was fed with commercial diet. At the same time, group 4, 5 and 6 were inoculated in the same manner with PBS and fed with commercial diet, containing 0.8% IOFP and 0.2% APS diet, respectively, as negative controls. At 0, 7, 14, 21, 28, and 35 days post-inoculation (dpi) firstly, the temporal changes in serum Newcastle disease hemagglutination inhibition (HI) and neutralizing antibody titers were determined. Meanwhile, proliferations of peripheral blood mononuclear cells (PBMCs) isolated from each group in response to concanavalin A stimulation and the expression levels of Th1-type (IFN-γ) and Th2-type (IL-4) cytokines were determined by 3-(4, 5-Dimethylthiazol-2-yl) −2, 5-diphenyltetrazolium bromide, and ELISA methods. On days 0, 14 and 28 after the first vaccination, the percentages of CD3 +, CD3 + CD8 +, and CD3 + CD4 + T lymphocytes were detected by flow cytometry. At 35 dpi, a challenge test was carried out and protective efficacy was determined. Results showed that oral administration of IOFP could significantly enhance ND HI and neutralizing antibody titers, proliferation of PBMCs, proportions of CD3 +, CD3 + CD8 +, and CD3 + CD4 + T lymphocytes, as well as the ratio of Th1/Th2, and all of these values were superior to those seen with APS as a positive control, and other groups. Therefore, IOFP possesses significant immune-potentiating properties in chickens and may be a more economical and convenient oral adjuvant to improve vaccination in avian species. Highlights: IOFP could improve adaptive immune responses effectively as immunopotentiator in avian. IOFP may be a more economical and convenient oral adjuvant to improve vaccination in avian species.